Stages of Hong Kong's democratic movement. Issue 4 (December 2019) - Tai, Benny Yiu-ting
Bill Moyer observed that there are eight stages in a social movement: seeming normal, exposing injustice, ripening conditions, taking off, losing heart, winning the majority, reaping success and consolidating achievement. For more than 30 years, Hong Kong people have been striving for democracy. Applying Moyer's model, Hong Kong should be now at a stage close to reaching its ultimate goal of establishing a genuine democratic system in the territory after years of work, especially the triggering event in September 2014 and the occupation during the Umbrella Movement. However, Moyer's model cannot be mechanically applied to the case of Hong Kong in light of the unique situation faced by Hong Kong people. Hong Kong's authoritarian sovereign holds the final key to Hong Kong's door to democracy. Unless there is a significant shift in the balance of powers in the Chinese polity, Hong Kong's democracy may be so near and yet so far.